NILAI-NILAI INTEGRITAS BISNIS DALAM HADIS SAW - Esti Rahmawati; Muhammad Alif (CV. Adiba Aisha Amira, 2026)
This study aims to examine the values of business integrity embedded in the hadiths of the Prophet Muhammad (peace be upon him) as an ethical foundation for Islamic economic practices. The academic problem addressed arises from the persistence of unethical business behaviors that contradict principles of honesty, justice, and moral responsibility, despite the availability of strong normative Islamic sources. This research employs a qualitative method using a library research approach, with data collected through thematic analysis of hadiths related to business activities and examined using content analysis techniques. The findings reveal that the Prophetic hadiths explicitly and implicitly emphasize core values of business integrity, including honesty in transactions, trustworthiness, fairness, transparency, and strict prohibitions against fraud and manipulation. These values function not only as moral guidelines but also as practical principles for fostering trust and ensuring business sustainability. The discussion highlights that integrating hadith-based integrity values into contemporary economic practices offers an ethical solution to modern business challenges and reinforces the relevance of hadith studies in the development of Islamic business ethics